The Occurrence of Hypertension in Adult Groups of Fishermen Families - Haria Sukma; Emy Yuliantini; Tetes Wahyu Witradharma (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
Hypertension is often called a silent killer because it triggers other deadly diseases and increases the risk of heart attack, heart failure, stroke, and renal failure. Risk factors of hypertension are genes, gender, age, race, obesity, sodium consumption, smoking, alcohol, less physical activity, stress, and caffeine consumption. The purpose of this research is to know the relationship of age, sodium consumption, body mass index (BMI), the ratio of hip waist circumference (RLPP) with the incidence of hypertension in adult groups of fishermen in the work area fish Market Puskesmas Kota Bengkulu Year 2019. The study used a descriptive-analytical design with a cross-sectional approach. The technique used is purposive sampling, with a sample number of 45 people aged (26-45 years). Statistical analysis is a chi-square test and logistics regression test. The results indicate the absence of age relations and RLPP with the incidence of hypertension (P-value > 0.05), there are IMT relations and sodium consumption with the prevalence of hypertension (p-value ≤ 0.05) and the most influential factor in the incidence hypertension, sodium ingestion (p-value 0.0005; OR 206, 28). Researchers advise people to reduce the consumption of high sodium foods.